The Influence of Relationship Marketing on Patient Loyalty Mediated by the Value Co-Creation Behavior of Patients at the Dental and Oral Education Hospital in Jakarta - Cathrine Rahayu (Journal of Social Research, 2023)
This study aims to analyze the influence of relationship marketing on patient loyalty mediated by the value co-creation of patient behavior which is divided into patient participation behavior and patient citizenship behavior in patients of the Educational Dental and Oral Hospital (RSGMP) in Jakarta. The data collection technique method uses non-probability sampling with a purposive sampling method. The respondents of the study as many as 310 people were patients who had received dental and oral care at least 2 times in the last 2 years at the RSGMP in Jakarta. The questionnaire was distributed via google form containing 31 statements answered based on five Likert scales. The analysis method used in this study is the Structural Equation Model (SEM). The results showed that relationship marketing has a positive effect on patient participation behavior and patient citizenship behavior. Patient participation behavior does not positively influence patient loyalty, but patient citizenship behavior has a positive effect on patient loyalty. Relationship marketing has a positive influence on patient loyalty. In addition, in the mediation variable, it was found that patient participation behavior does not have a mediating influence between relationship marketing on patient loyalty, while patient citizenship behavior has a partial mediation influence.